Analysis of Marketing Strategies in China of Imported Small Household Appliances Based on Advertising Communication —— Taking Dyson Hair Dryer as an Example - Wang, Jingting (Transactions on Social Science, Education and Humanities Research, 2024)
The rise of China's economy and the improvement of people's living conditions have contributed to an increasing market demand for small home appliances in the nation. Importing companies face significant challenges when entering the Chinese market, necessitating meticulous and comprehensive marketing strategies, especially in the realm of advertising communication. The Dyson hair dryer, a domestically manufactured appliance, has attracted considerable consumer attention and attained noteworthy accomplishments within the Chinese market. The research findings indicate that Dyson's successful advertising communication strategy in the Chinese market stems from its use of innovative advertising formats, emotional brand positioning, and precise targeting of specific client categories. This study uses a thorough research methodology, including comparison analysis, case analysis, and other techniques, to investigate the effectiveness and influence of Dyson's advertising communication strategy in the Chinese market. We use secondary data to conduct relevant qualitative analysis. The aforementioned study serves as a great asset in shaping the marketing strategy for imported small home appliances in the Chinese market. Moreover, it functions as a valuable point of reference and source of inspiration for forthcoming marketing strategies for analogous products.